Value co-creation as determinat of succcess in crowd-funding experiencesin the cultural sector - Quero-Gervilla, María José; Ventura-Fernández, Rafael; Santoja, Antonio (My University, 2014)
The aim of the present study is to analyse the role of value co-creation on success crowd-funding experiences in the cultural sector. The relationships developed between actors can be considered as a type of collaborative behaviour model, which makes use of the potential offered by new technologies in actors who get order to benefit everyone. The analysis of the structure of the relationships between actors who get involved in crowd-funding is approached with the primary objective of finding out which are the factors that explain crowd-funding as a balanced system of co-creation relationships. Specifically, the focus of the research is on the interactions between system actors, whose roles we will attempt to define: what do they contribute and what do they gain from the system, and how do they achieve the balance that leads them to continue the relationship.
Keywords: Cultura - Aspectos económicos; Arte - Aspectos económicos; Arte - Marketing; Co-creation; Service-dominant logic; Arts marketing; Balanced centricity; Service management